Chemical Reagents for Protein Modification - Lundblad, Roger L. ([S.l.] : CRC Press, 2014)
The use of the chemical modification of proteins has evolved over the past 80 years, benefiting from advances in analytical, physical, and organic chemistry. Over the past 30 years, the use of chemical reagents to modify proteins has been crucial in determining the function and structure of purified proteins. This groundbreaking work is part of the foundation of emerging disciplines of proteomics, chemical biology, structure biology, and chemical proteomics. Chemical Reagents for Protein Modification, Fourth Edition provides a comprehensive review of reagents used for the chemical modification of proteins, representing a major revision of the work presented in previous editions. The completely updated Fourth Edition is substantially larger and includes five new chapters: Alkylating Agents Acylating Agents Nitration and Nitrosylation Oxidation Modification of Proteins with Reducing Agents There is greatly increased coverage of the chemical modification of cysteine, which is critical for bioconjugate synthesis. The chapter on reduction also provides information necessary for bioconjugate synthesis as well as for the processing of inclusion bodies. The book places emphasis on conditions that affect the specificity of the chemical modification of proteins, such as solvent and temperature. The format has been markedly revised, presenting information based on the chemical nature of the modifying material and on the amino acid residue modified. This new version has increased significance to biopharmaceuticals. Much of the information is in tabular form, which enables the rapid location of cited material.
Keywords: Chemical modification; Chemical tests and reagents; Protein engineering; Proteins; v